Determinan Makroekonomi terhadap Pembiayaan Bermasalah pada Bank Umum Syariah di Indonesia: Bukti Data Panel 2021-2025 - Adinda Putri Kamalia; Maidalena Maidalena; Nuri v (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2026)
This study examines the partial and simultaneous effects of inflation, the BI Rate, the rupiah exchange rate, and Gross Domestic Product (GDP) on Non-Performing Financing (NPF) in Islamic Commercial Banks in Indonesia during the 2021-2025 period. Employing a quantitative panel-data approach, the study uses data from Islamic Commercial Bank financial reports, Bank Indonesia, and the Central Statistics Agency. The population consists of 14 Islamic Commercial Banks listed in the 2025 Islamic banking statistics of the Financial Services Authority, with 12 banks selected through purposive sampling based on full operational status and complete financial-report availability throughout the observation period. The data were analyzed using panel-data multiple linear regression with EViews 12.0 according to the selected estimation model. The findings show that inflation and the BI Rate have negative and significant partial effects on NPF, whereas the rupiah exchange rate and GDP have no significant effect. Simultaneously, the four macroeconomic variables significantly affect NPF, with an Adjusted R-squared value of 67.35%, indicating that the model explains most of the variation in NPF, while the remainder is influenced by factors outside the study.